Genetic markers in oligodendroglial tumours - Velnar, Tomaž (Radiology and oncology (Ljubljana), 2010)
Background. Oliogodendrogliomas are brain tumours composed of the cells resembling oligodendrocytes. They represent the third most common glial tumour, comprising 2.5% of all primary brain tumours and 5-20% of all gliomas. Conclusions. Oligodendroglial tumours with 1p and 19q loss demonstrate a better overall prognosis due to more indolent clinical behaviour and higher sensitivity to treatment. Additionally, 1p and 19q loss is a marker of clinical utility, helping to assess tumour sensitivity to chemotherapy and harbouring the potential for improving the diagnosis and survival of oligodendroglioma patients as well as future clinical practice.
Keywords: Diagnosis; Diagnostika; Epidemiologija; Epidemiology; Etiologija; Etiology; Genetic markers; Genetski markerji; kemoterapija; markerji; možgani; Neoplasms; Novotvorbe; Oligodendroglia; Oligodendroglija; onkologija; prognoza; Therapy; tumor; Zdravljenje